Redescription of two species of Asterocheres Boeck, 1860 (Copepoda: Siphonostomatoida), A. corneliae Schirl, 1973 and A. boeckii (Brady, 1880), and proposal of a new genus for Asterocheres fastigatus Kim, 2010 - Bandera, Eugenia; Conradi, Mercedes (Zootaxa, 2016)
Asterocheres Boeck, 1860 is the largest genus in the family Asterocheridae and includes approximately 96 nominal species. Nevertheless, according to Kim (2010), the current assignment of twelve of these species to Asterocheres is debatable, and fifteen species are too incompletely described for reliable comparisons to be made. In this paper, two species, A. corneliae Schirl, 1973 and A. boeckii (Brady, 1880), are redescribed and compared with their congeners. As a result of the comparison between A. boeckii and A. fastigatus Kim, 2010, a new genus, Kimcheres, is erected to accommodate the only species of Asterocheres displaying the armature formula (0-1) on the second endopodal segment of leg 4. The taxonomic position of A. longisetosus Nair & Pillai, 1984, considered as species inquirenda by Kim (2010), is discussed. Examination of the original description and illustrations, especially the antennules and the mandible, casts doubts on the validity of the species. Asterocheres Boeck, 1860 is the largest genus in the family Asterocheridae and includes approximately 96 nominal species. Nevertheless, according to Kim (2010), the current assignment of twelve of these species to Asterocheres is debatable, and fifteen species are too incompletely described for reliable comparisons to be made. In this paper, two species, A. corneliae Schirl, 1973 and A. boeckii (Brady, 1880), are redescribed and compared with their congeners. As a result of the comparison between A. boeckii and A. fastigatus Kim, 2010, a new genus, Kimcheres, is erected to accommodate the only species of Asterocheres displaying the armature formula (0-1) on the second endopodal segment of leg 4. The taxonomic position of A. longisetosus Nair & Pillai, 1984, considered as species inquirenda by Kim (2010), is discussed. Examination of the original description and illustrations, especially the antennules and the mandible, casts doubts on the validity of the species.